The Entertainment Media And The Preservation Of The Igbo Language And Culture (Eurasian Journal of Media and Communications, 2025)
This paper strives to explore some aspects of Igbo cultural heritage that are gradually moving into extinction, if not extinct. It also looks at the attitude of Nigerians (the Igbo) towards their God-given language and culture. Studies in language endangerment have revealed that no Nigerian language is safe. A language loss is a culture loss as language and culture are intertwined. Research has also proved that the native speakers' attitude is the primary cause of this problem. On the other hand, media scholars have put the problem of eroding culture and the language attitude on the activities of Nigerian mass media especially in the area of video films and music. This paper, therefore, takes the position that despite the shortfall of the mass media in promoting and sustaining indigenous culture, the Nigerian mega entertainment media industry, Nollywood, with the needful re-orientation, can still be used to redirect the focus of the Nigerian (Igbo) youths back to their original cultural heritage in which case, the indigenous language and culture would be preserved. The paper primarily draws its data from library works in addition to intuition and observation. Development media and cultural imperialism theories are adopted as the theoretical frameworks while the research design is the needs assessment survey